Network City: Retrofitting the Perth Metropolitan Region to Facilitate Sustainable Travel - Curtis, Carey (Routledge - Taylor and Francis Group, 2006)
‘Network City’, the latest 25-year planning strategy for metropolitan Perth, Western Australia, is designed to realise the integration of land use and transport networks within established and new areas. This article examines the influence of urban form on travel patterns and the case for sustainable travel outcomes in order to set in context the ‘Network City’ concept. The concept is described, and then the article focuses on the operational detail needed to progress towards fuller integration between the transport network and the city it serves. This includes analysis of urban structure in the context of the factors that influence efficient use of public transport: including residential density, intensity of activity and the hierarchy of activity centres. The implications for road planning are discussed where land use–transport integration is the core objective rather than simply traffic efficiency. If sustainable travel is to be facilitated there is a need to change both the operation of public transport and the urban structure and these changes are mutually supportive.